2002
DOI: 10.1111/j.1365-2621.2002.tb08787.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Catfish Fillets with Citric Acid Causes Reduction of 2‐Methylisoborneol, but not Musty Flavor

Abstract: Catfish fillets containing 2-methylisoborneol were vacuum-tumbled in 0%, 0.5%, and 2% citric acid solutions, or left untreated to evaluate acid treatment for reducing musty flavor. Color, texture, composition, and expressible moisture were determined using raw fish. Untreated and 2% acid-treated cooked fish were evaluated by sensory evaluation. MIB, determined by GC-MS, significantly decreased from 4.43 to 2.80 mg/kg as a result of vacuum-tumbling with 2% citric acid. The moisture content, expressible moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This reduction is similar to those reported by Yamprayoon and Noomhorn (2000) and Forrester and others (2002). Yamprayoon and Noomhorm (2000) reported 35% reduction of GEO for smoked tilapia placed in 7% acetic acid brine solution for 2 wk.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This reduction is similar to those reported by Yamprayoon and Noomhorn (2000) and Forrester and others (2002). Yamprayoon and Noomhorm (2000) reported 35% reduction of GEO for smoked tilapia placed in 7% acetic acid brine solution for 2 wk.…”
Section: Resultssupporting
confidence: 88%
“…Yamprayoon and Noomhorm (2000) reported 35% reduction of GEO for smoked tilapia placed in 7% acetic acid brine solution for 2 wk. Forrester and others (2002) reported 36% reduction of MIB in catfish vacuum tumbled in 2% citric acid. The reductions in the current study, however, are much less than those reported by Mireles DeWitt and others (2007b).…”
Section: Resultsmentioning
confidence: 99%
“…After 2 d of refrigerated storage, the fish fillets were cut into pieces (2.5 cm × 2.5 cm) and breaded (item number: B5APV2, Newly Weds Foods). The fillet pieces were then prepared in a 4 L Cool Zone Deep Fryer (Oster Corp., Boca Raton, Fla., U.S.A.) at 174 °C for 3 min (Forrester and others 2002). The 4 fried catfish treatments were assessed by a panel of 6 members with prior muscle food sensory evaluation experience.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the variation in geosmin and MIB content from rep to rep seems a bit extreme. However, Forrester et al (2002) obtained their catfish by subjectively screening for off-flavor (specifically MIB), and these catfish ranged from 1-8 ppb MIB when quantitatively analyzed by GC-MS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few attempts to remove off-flavors in catfish using post-harvest as opposed to pre-harvest controls. Forrester et al (2002) treated catfish fillets with 0.5 and 2% citric acid solutions to reduce MIB. Citric acid was applied by vacuum tumbling treated fillets for 10 min.…”
Section: Discussionmentioning
confidence: 99%